Professional Training of Future Teachers for the Development of Speech Activity of Younger Schoolchildren - Sapargaliyeva, Aizhan Zh.; Muratbekova, Dinara Ye.; Aralbaeva, Ryszhamal K.; Zhakipbekova, Saule S.; Shynybekova, Aizhan S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The purpose of the experiment was to determine the level of knowledge of future primary school teachers about dialogical speech in the lessons of a discipline “Self-knowledge” (content component), their ability to apply this knowledge in the process of developing the dialogical speech of primary school students with mental disorders (operational component) and the comprehensive using of knowledge about dialogical speech in the process of educational activity (motivational component). Background: Professional training of future teachers of primary schools is currently one of the pressing problems in modern Kazakhstan. One such way is the introduction of a practice-oriented competence of the future primary school teacher. This involves the formation of professional competence of a primary school teacher, his ability to solve typical professional problems on the basis of acquired knowledge and experience. Method: For determining the preparation of future primary school teachers for work on the development of dialogical speech of primary school students a pedagogical experiment consisting of ascertaining and formative stages was conducted. Results: Scientific research on the methodology of speech development is aimed at finding methods, techniques, and forms of training that increase the effectiveness of such important components of the learning content as language and speech competence, which are part of the communicative competence of pupils. In scientific pedagogy and psychology, the purpose of education and training is to develop a child’s personality. The development of personality is considered as a long process of acquiring the culture of the people. Speech culture is an integral part of the general culture, so speech development is the most important task of forming the personality of a preschool and primary school pupil. The key role in psychological development is played by external, oral, monological, dialogical, and written speech. Conclusion: Interrelation of the investigated components can serve as a description of the level of preparedness of future primary school teachers.